Apple polyphenol extract targets circadian rhythms to improve liver biological clock and lipid homeostasis in C57BL/6 male mice with mistimed high-fat diet feeding. (May 2022) - Cui, Yuan; Yin, Yan; Li, Shilan; Xie, Yisha; Wu, ZhengLi; Yang, Hao; Qian, Qingfan; Li, Xinli
Graphical abstract: To the best of our knowledge, this is the first study to explore the novel ability of apple polyphenol extract to target circadian rhythms in the regulation of hepatic biological clock and lipid homeostasis. Highlights: Mice were fed according to four different feeding patterns and the interactive effects of feeding time and food composition were studied. This was the first study of the capacity of one of the polyphenolic compounds, apple polyphenol extract (APE), to target circadian rhythms to improve hepatic biological clock and lipid homeostasis in C57BL/6 male mice with mistimed HFD feeding. APE treatment significantly improved the increase in body weight, liver weight and fat accumulation mediated by daytime HFD feeding in the short term. APE treatment regulated the rhythmic expressions of hepatic circadian clock genes, and genes related to lipid and bile acid metabolism. Abstract: To investigate the potential role of apple polyphenol extract (APE) in the prevention and alleviation of circadian rhythm disturbances, eighty male C57BL/6 mice fed a high-fat diet (HFD) were randomized into four groups: 24 h ad libitum feeding (AL), 12 h restricted nighttime feeding (NF) or daytime feeding (DF), and daytime feeding with APE intragastric administration (DF-APE). Five weeks later, the mice were sacrificed at 6 h intervals over 24 h. Disrupted fluctuations in serum lipid profiles and hormones, along with desynchronization of circadian clock genes and metabolic genes were observed after daytime HFD feeding. However, APE treatment improved hepatic steatosis and recovered circadian rhythms of Cry1/2, and genes Acc and Hsl related to lipid synthesis and hydrolysis of cholesteryl esters, and Cyp7a1 in bile acid synthesis. In conclusion, the present study provides new evidence revealing that the circadian clock might be a novel target for APE to regulate metabolic homeostasis.